2021
DOI: 10.1107/s2053229621008275
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical synthesis insights and solid-state characterization of quininium aspirinate, a glass-forming drug–drug salt

Abstract: Quinine (an antimalarial) and aspirin (a nonsteroidal anti-inflammatory drug) were combined into a new drug–drug salt, quininium aspirinate, C20H25N2O2 +·C9H7O4 −, by liquid-assisted grinding using stoichiometric amounts of the reactants in a 1:1 molar ratio, and water, EtOH, toluene, or heptane as additives. A tetrahydrofuran (THF) solution of the mechanochemical product prepared using EtOH as additive led to a single crystal of the same material obtained by mechanochemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 43 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Pioneer studies have demonstrated this for the syntheses of ZIF-6 (a MOF) [128], 2,3-diphenylquinoxaline [129], and the Diels-Alder cycloaddition of cyclopentadiene and N-4-tolylmaleimide [130]. The author has also observed that for the neat mechanochemical synthesis of quininium aspirinate, reactant consumption increases from partial to complete with a milling frequency increase from 10 to 30 Hz [85]. Although in some publications these effects have been interpreted based on increased amounts of mechanical energy input at increasing milling frequencies, quantitative relationships remain poorly explored.…”
Section: The Insufficiently Characterized Energy Input In Ball Millin...mentioning
confidence: 90%
See 3 more Smart Citations
“…Pioneer studies have demonstrated this for the syntheses of ZIF-6 (a MOF) [128], 2,3-diphenylquinoxaline [129], and the Diels-Alder cycloaddition of cyclopentadiene and N-4-tolylmaleimide [130]. The author has also observed that for the neat mechanochemical synthesis of quininium aspirinate, reactant consumption increases from partial to complete with a milling frequency increase from 10 to 30 Hz [85]. Although in some publications these effects have been interpreted based on increased amounts of mechanical energy input at increasing milling frequencies, quantitative relationships remain poorly explored.…”
Section: The Insufficiently Characterized Energy Input In Ball Millin...mentioning
confidence: 90%
“…Drug-drug combinations with synergistic properties (often salts or cocrystals) have been also prepared using mechanochemistry [84,85]. In comparison with cocrystal syntheses from solutions, mechanochemical reactions are advantageous toward avoiding problems due to the low solubility of any of the individual coformers.…”
Section: Scheme 2 a Few Selected Examples Of Inorganic Mechanochemica...mentioning
confidence: 99%
See 2 more Smart Citations